POJOK PAJAK: BAKTI RELAWAN PAJAK (RENJANI) UNTUK MASYARAKAT - Agustina, Rachma; Pertiwi, Dwi Ari; Ardiana, Meta; Humaidi; Husna, Lia Safarotul; Srikalimah (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
The Tax Volunteer Program at Universitas Hasyim Asy’ari aims to increase tax awareness in the community through assistance with Annual Tax Return (SPT) filing. This initiative involves students as volunteers who undergo intensive training in taxation, including SPT filing procedures and the tax volunteer code of conduct. During the February–March 2025 period, the volunteers assisted approximately 800 taxpayers at various locations, in collaboration with the Jombang Primary Tax Office (KPP Pratama Jombang). Evaluation results indicate that the program ran successfully and made a significant contribution to supporting taxpayer compliance, with success measured by activity scores validated by the Directorate General of Taxes of the Republic of Indonesia. As a follow-up, a “Tax Goes to School” program is planned to instill tax awareness from an early age. This program not only supports the Directorate General of Taxes but also enriches students’ experience in community service in line with the Tri Dharma of Higher Education.